EFFECT OF ADDING DIFFERENT LEVELS OF RAW POWDERED MULBERRY AND ARTICHOKE LEAVES, AND THEIR COMBINATION, ON LIVER ENZYMES AND CERTAIN OXIDATIVE STRESS MARKERS IN LAYING HENS EXPOSED TO HEAT STRESS - Ali, Nashwan Majeed (PT. Antis International Publisher, 2025)
Objective: This study aimed to investigate the biological effects of dietary supplementation with mulberry and artichoke leaves on mitigating the negative impacts of heat stress in laying hens. Method: A total of 144 Lohmann Brown laying hens were randomly assigned to six dietary treatments (24 hens per treatment, three replicates of eight hens each). The treatments consisted of a basal diet supplemented with artichoke leaf powder, mulberry leaf powder, or their combination at inclusion levels of 0, 1, 1.5, 1, 1.5, and 1.5+1.5 g/kg of feed, respectively. The trial lasted four months, during which blood samples were collected biweekly from each replicate, and monthly averages were analyzed to evaluate liver enzyme activities (AST, ALT, ALP) and oxidative stress markers (MDA, SOD). Results: The findings revealed that dietary supplementation with mulberry and artichoke leaves, individually or in combination, significantly alleviated the adverse effects of heat stress, as reflected by improved oxidative status and more favorable liver enzyme activity. Novelty: This study highlights the functional potential of natural plant-based additives, such as mulberry and artichoke leaves, as sustainable nutritional strategies to enhance resilience and maintain performance of laying hens under heat stress conditions.